2021
DOI: 10.1088/1742-6596/1767/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of gold price with ARIMA and SVM

Abstract: Gold has become more popular as well as very useful commodity in terms of investment. Gold has been used as a national reserve for many years, and that makes it very crucial in the economics of any country. Most of the investors running to gold as a safe area from uncertainty and political chaos. Determining of the price movement of gold helps the investors in focus in their investments, government to make correct decision about economy since Gold price is a key element is world economy. For the purpose of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 9 publications
0
15
0
3
Order By: Relevance
“…LR remained a favorite choice for gold price prediction. Bingol et al [10] have introduced an approach to surveying the relationship of the gold rate with several descriptive variables that tend to be measured as signs of geopolitical and economical disasters. The study has surveyed the probability of forecasting gold rates.…”
Section: Linear Regression (Lr)mentioning
confidence: 99%
“…LR remained a favorite choice for gold price prediction. Bingol et al [10] have introduced an approach to surveying the relationship of the gold rate with several descriptive variables that tend to be measured as signs of geopolitical and economical disasters. The study has surveyed the probability of forecasting gold rates.…”
Section: Linear Regression (Lr)mentioning
confidence: 99%
“…SVM has been applied in various domains for price forecasting, such as crude oil [44][45][46][47], rubber [48], gold [49], and electric [50][51][52][53], agricultural [54], and stock [55] from 2005 to 2021. SVM can avoid the over-fitting problem and model the nonlinear relationships stably, as it applied the risk minimization principle in training.…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
“…SVM can avoid the over-fitting problem and model the nonlinear relationships stably, as it applied the risk minimization principle in training. SVM has been tested and compared to statistical models such as ARIMA and has shown a better performance [47,49]. The interpreted result suggests that SVM performs better for capturing nonlinear relationships and in handling irregularities than statistical models.…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
“…For more than 2000 years, gold has been known as a high-quality liquid asset that has served as a hedge and safe haven for exchanging commodities. Several robust statistical models have been proposed to explore the predictability of the gold price [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the performance of the SVM-PSO technique is better than the SVM algorithm. The ARIMA and SVR models were employed in [ 3 ] to predict the daily price of gold, whereas in [ 30 ], the SVC model was utilized to predict whether the price of three cryptocurrencies (BTC, ETH, and LTC) would increase or decrease in the next day.…”
Section: Introductionmentioning
confidence: 99%